Evaluation of lentiviral vector stability and development of ion exchange purification processes. (3rd August 2022) - Ghosh, Ronit; Koley, Sushmita; Gopal, Sneha; Rodrigues, Andre L.; Dordick, Jonathan S.; Cramer, Steven M.
Abstract: In this manuscript, we employ parallel batch stability and chromatographic screens in concert with linear and step gradient experiments to develop a high yield, HCP clearance anion exchange capture process for lentiviral vector (LVV) purification. An initial broad resin screen is carried out to determine anion exchange‐based resins that exhibit high recovery of LVV. LVV stability is then evaluated and conditions are established where the vector exhibits good stability, namely phosphate buffer at pH 6.5–7.5, with low to moderate salt concentrations. A subsequent high‐throughput batch screen is then carried out with a subset of resins selected from the first screen under stable conditions to identify optimal wash and elution steps to further improve product yield and protein clearance. Linear gradient experiments are also conducted in mini‐column format to refine the operating conditions and final step gradient processes are established that exhibit greater than 70% yield of infectious LVV while also achieving up to 2.89 log reduction values (LRV) of HCPs during the process. The large set of stability and chromatographic data provided in this work represent an important contribution to knowledge in the field about the chromatographic efficacy of a wide range of resins for LVV bioprocessing under stable conditions.